The Impact of Dark UX on E-Commerce Consumer Decisions: A Qualitative Analysis and Ethical Design Recommendations - Hendri Purnomo; Firmansyah; Ari Rudiyan (Hanif Journal of Information Systems, 2026)
Dark UX is an interface design practice that manipulates users into taking actions that benefit the service provider, often at the expense of the consumer. This study explores how dark UX influences consumer decision-making in e-commerce applications, identifies user issues, and develops recommendations for developers. A qualitative approach with purposive sampling was used to select 15 informants aged 25-45 who actively shop through e-commerce applications. Data were collected through in-depth semi-structured interviews and document analysis, then analyzed using thematic coding using Miles and Huberman's interactive model. Findings indicate that misleading urgency (limited stock notifications), sneak-into-basket (automatic item additions), and roach motel patterns (cancellation barriers) induce significant psychological distress, particularly the fear of missing out, which drives impulse purchases. Hidden costs that emerge only at the checkout stage and manipulated product reviews also erode user trust. The study recommends the implementation of ethical design principles, including up-front price transparency, easy-to-understand terms and conditions, real-time behavioral interventions, and regular dark UX audits. Stronger regulations and digital literacy programs are needed to create a healthy and sustainable e-commerce ecosystem.